Recursos Educacionais Abertos (REA) nas teses e dissertações brasileiras entre 2002 e 2019 / Open Educational Resources (OER) in Brazilian theses and dissertations between 2002 and 2019 - Rosiclei Aparecida Cavichioli-Lauermann; Elena Maria Mallmann (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2023)
An analysis of the research scenario on integrating OER in the teaching-learning process is systematized. We analyzed 118 pieces of research produced in Brazil from 2002 to 2019, composing a set of 25 dissertations, 57 academic theses, and 36 professional theses. The texts were extracted from the databases of the CAPES Catalog of Dissertations and Theses and the Digital Library of Dissertations and Theses (BDTD, from the Portuguese Biblioteca Digital de Teses e Dissertações). The scenario design started from the aggregation of results focusing on a) the temporal evolution of the research, b) the localities, c) the administrative dependence of the Teaching Institutions, and d) the area of knowledge. Complementarily, the findings from the four guiding questions made it possible to conclude that there were few pieces of research investigating the integration of OER in the teaching-learning process, especially within the context of Technical and Vocational Education (TVE) and Graduate School. Moreover, the study revealed that, among the 5Rs of OER, the practice most promoted by the pieces of research within the scope of the teaching-learning process was reuse, which is directly associated with retain and redistribute. This indicates the need to expand and strengthen the continuing education actions aimed at the practice of the other two Rs: revise and remix. Finally, the study pointed out the need for research that performs articulations with educational public policies so that they may generate creation and sharing, in addition to consolidating the international open education movement.